Association between the Cardio-Ankle Vascular Index and Executive Function in Community-Dwelling Elderly People - Misu, Shogo; Saito, Takashi; Nakatsu, Nobuyuki; Sawa, Ryuichi; Nakakubo, Sho; Nakamura, Ryo; Sugimoto, Taiki; Murata, Shunsuke; Ono, Rei; Ueda, Yuya (Journal of Atherosclerosis and Thrombosis, 2016)
Aim: The aim of this study was to investigate the cross-sectional association between arterial stiffness (AS) measured with the cardio-ankle vascular index (CAVI) and executive function in community-dwelling elderly people. Methods: Subjects were 140 community-dwelling elderly people who participated in the study at Kobe, Japan during the period of August–September 2014, of which 126 (mean age±SD: 73.2±6.1, female: 67.5%) met the inclusion criteria and completed the study. Age, sex, body mass index, global cognition, existence of chronic disease, medication, smoking history, and years of education were assessed. The degree of AS was assessed using CAVI. Executive function was assessed using the Category Word Fluency Test (CWFT), Letter Word Fluency Test (LWFT), and Digit Symbol Substitution Test (DSST). We used a correlation analysis and multiple linear regression analysis to investigate whether higher CAVI was independently associated with lower executive function. Results: In the univariate analysis, higher mean CAVI correlated with lower CWFT (rho=－0.21, p=0.020), LWFT (rho=－0.32, p＜0.001), and DSST (rho=－0.31, p＜0.001). In the multivariate analysis, higher mean CAVI was associated with lower LWFT (β=－0.21, p=0.046) after adjusting for confounding factors, although there was no association with CWFT (β=－0.05, p=0.61) and DSST (β=－0.06, p=0.51). Conclusions: We found that high CAVI was associated with lower LWFT. These results suggest that arterial stiffness is associated with lower performance in phonemic fluency.